(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Ethnic diversity in relation to ABO and rhesus blood systems are yet to be determined for multiethnic areas of Khagrachari, Bandarban and Cox’s bazaar districts of Bangladesh. Therefore we aimed to characterize the genetic characteristics of ABO and rhesus blood systems from population of these districts. Materials and methods: It was a retrospective descriptive study conducted in Khagrachari, Bandarban, and Cox’s Bazaar district. From hospital blood bank register we obtained ABO and rhesus blood groups related information. They were segregated by ethnicity and allele, genotypic and phenotypic distributions were calculated using the Herdy-Weinberg formula. Results: Six patterns of phenotypic frequency were observed. B > O > A > AB and O > B > A > AB were the most frequent phenotype pattern. Highest I A was in Chak (0.3300), I B in Tripura (0.4883) and I O in Khumi (0.7475). Among the Bengali highest I A was 0.1738 (Cox’s Bazar), I B was 0.2644 (Khagrachari) and I O was 0.6292 (Cox’s Bazar). Rhesus negative group were scarce (0.1 to 2.7%). Conclusion: Remarkable ethnic variation exists in genetic pattern of ABO and rhesus blood systems among population from the studied areas. JCMCTA 2023 ; 34 (2) : 51-55